A collaborative framework for social media aware manufacturing. (January 2015) - Andreadis, Georgios
Abstract: The growing use of internet could make product manufacturing a collaborative and collective process. Social media provide the opportunity to many businesses to optimize the manufacturing process, by taking into consideration the needs, the background and the experiences of a wider external audience. The paper proposes a framework using social media combined with a Live Streaming process, in order to optimize: (a) the design process (CAD) of a product, using the opinions of potential customers and (b) the manufacturing process (CAM) of a product, and more specifically the selection of cutting conditions, using the experience of other external expert technicians.